Proposal of a specific classification of primary periphyseal stress injuries in adolescent rock climbers - Schöffl, V.; Iruretagoiena, X.; Nelson, T.; Miro, P. (Frontiers in Sports and Active Living, 2025)
Introduction: Primary Periphyseal Stress Injuries (PPSI) of the hand and fingers are relatively uncommon but are most frequently seen in adolescent rock climbers. A major limitation in the current literature on PPSIs is the lack of a standardized nomenclature and radiological classification. This gap complicates the accurate diagnosis, treatment, and comparison of outcomes across studies.